Sweeteners Pharmacology, Biotechnology, and Applications (Reference Series in Phytochemistry, 2018)
This handbook compiles comprehensive reference information on sweeteners for academic researchers and professionals. It discusses both natural as well as synthetic products, considering health-related and economical aspects. Renowned authors mostly from academia, but also from the industry, summarize information about the chemistry, biological and pharmacological aspects, as well as bioavailability and applications of sweeteners. The book introduces various substance classes of sweeteners, which are mainly plant-derived, including glycosidic and terpenoid sweeteners, peptidic sweeteners, sweet-tasting proteins and protein-derived sweeteners (e.g. stevioside, sucralose, aspartame, thaumatin, brazzein and many more). Chapters address topics such as the isolation and purification of the compounds, their physical, chemical and biological properties, pharmacological activities, and also critically discuss their applications in view of health and ecotoxicological aspects. A special emphasis is on low or no-calorie sweeteners, for which there is an increasing demand and intensified research activities currently. This reference work hence provides the readers with key information and will serve the needs of graduate students and scholars, researchers and professionals working in the fields of chemistry, botany, biotechnology, or pharmacological or agricultural research, as well as in the food industry or the marketing of sweeteners.